PENERAPAN MODEL PROBLEM BASED LEARNING PADA PELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS II DI SD NEGERI TLOGO TAHUN PELAJARAN 2021/2022 - Febriyani Dyah Wulansari; Uus Kusdinar; Subagya , Subagya; Subiyanta, Subiyanta (Badan Penerbit STIEPARI Press, 2022)
Based on the results of research observations conducted in class II of Tlogo Elementary School for the 2021/2022 academic year, the learning conditions during the pandemic in class did not work as expected. Student activities in learning were just listening to requests for material from the teacher and doing assignments from the teacher, 15 out of 2 students were not active during group discussions, did not even complete student worksheets that had been given by the teacher and also did not dare to give responses or ask and answer questions friends doing presentations. As a result, in these group activities only a few students actively dominated both during the discussion process, completing assignments and. When showing the results of discussions and the results of group work. This can be said as a condition that shows low student learning activity. Based on these problems, it is necessary to take corrective action in learning to increase student activity and learning outcomes. One of them is by applying the problem-based learning model. Problem-based learning is one of the learning methods described in the 2013 curriculum section. The problem-based learning method is a learning model that is based on many things that require authentic investigation, namely investigations that require a real solution to a problem.